The conserved AAA-ATPase PCH-2 (TRIP13) regulates spindle checkpoint strength - Défachelles, Lénaïg (Mol Biol Cell, 2020)
Spindle checkpoint strength is dictated by the number of unattached kinetochores, cell volume, and cell fate. We show that the conserved AAA-ATPase PCH-2/TRIP13, which remodels the checkpoint effector Mad2 from an active conformation to an inactive one, controls checkpoint strength in Caenorhabditis elegans. Having previously established that this function is required for spindle checkpoint activation, we demonstrate that in cells genetically manipulated to decrease in cell volume, PCH-2 is no longer required for the spindle checkpoint or recruitment of Mad2 at unattached kinetochores. This role is not limited to large cells: the stronger checkpoint in germline precursor cells also depends on PCH-2. PCH-2 is enriched in germline precursor cells, and this enrichment relies on conserved factors that induce asymmetry in the early embryo. Finally, the stronger checkpoint in germline precursor cells is regulated by CMT-1, the ortholog of p31(comet), which is required for both PCH-2′s localization to unattached kinetochores and its enrichment in germline precursor cells. Thus, PCH-2, likely by regulating the availability of inactive Mad2 at and near unattached kinetochores, governs checkpoint strength. This requirement may be particularly relevant in oocytes and early embryos enlarged for developmental competence, cells that divide in syncytial tissues, and immortal germline cells.